Do the village financial system application and quality of financial reports in Kediri regency matter? - Nisa Mutiara; Eka Askafi; Wawan Herry Setyawan (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2022)
The study aimed to determine how implementing the Village Financial System (Siskeudes) application affects transparency as a mediator in realizing quality village financial reports in Kediri Regency. The quantitative research used secondary data as a questionnaire to the Village Treasurer in Kediri Regency. Purposive sampling was used to carry out the sample selection process, and 343 villages provided 185 samples for the study through a regression model. The results show that the Siskeudes application can directly affect the quality of village financial reports and indirectly through transparency as a mediating variable. The Siskeudes application significantly impacts the caliber of village financial reports; transparency can augment this impact as a mediating factor.